Buddies Shoppe / Ahmad Azhar Baharudin ... [et al.] - Baharudin, Ahmad Azhar; Zulkifli, Mohd Najib; Mohamed Sharif, Mohd Shah; Kamaruddin, Mohd Faizul Fadli; Kamarudzaman, Azrul Hisyam (Faculty of Information Management, 2002)
Business field and entrepreneurship world is one of the economical activities, which ensure profit but surely need courage and effort to be successful in the project. As well as self confident a person also have to be creative, sensitive to any opportunity, motivated, innovative and must always beware towards the competitive world of business. Business can be taken as a guide for an individual to create a new product or service to the customers. Normally those activities did for profits. Although part of its done only for profits but all of them play a vital role in increasing the life status of the community from time to time.